The Concept of Microbes as Jinn : (A Comparative Study of the Methods of Interpretation of Verses about Satan in Tafsir Al-Manar) - Bannan Naelin Najihah; Gilang Reza Permana (Journal of Ulumul Qur'an and Tafsir Studies, 2023)
In Qur’an several verses describe Satan as a human enemy with negative traits. In traditional commentaries, Satan is described as a jinn or even human-type entity. However, an innovative view came from Muhammad Abduh. He interpreted jinn and satan uniquely, relating them to microbes or microorganisms visible through a microscope. This study aims to explore the views of Muhammad Abduh and Rashid Ridha in tafsir Al-Manar regarding the verses of Satan. The research also reveals a comparison of their interpretation methods in linking Satan with the concept of microbes. This variation in interpretation can be understood through personal background, education, teacher influence, and the social, political and cultural context during their lifetime. The research method used is literature and content analysis. Data from various literatures are used for descriptive analysis and logical interpretation. The results of the analysis show two views in Al-Manar's interpretation of the verse on jinn and Satan. The first view, in line with the predecessor's interpretation, considers Satan as an evil jinn that is invisible because of its kind. Muhammad Abduh's view gives a new dimension, maintaining the concept of Satan as a jinn and adding it as a microbe that causes disease. Both interpretations use the bil ra'yi argumentation method with a comparative style and use a scientific approach.